2011
DOI: 10.1001/archpediatrics.2011.64
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Determinants of Tobacco Use Disparities in Lesbian, Gay, and Bisexual Youth

Abstract: Objective:To determine whether characteristics of the social environment surrounding lesbian, gay, and bisexual (LGB) youth contribute to their rates of tobacco use after controlling for established community-level risk factors.Design: Cross-sectional.Setting: Population-based study of youth.Participants: A total of 31 852 eleventh-grade students (1413 LGB individuals [4.44%]) in Oregon completed the Oregon Healthy Teens survey in 2006-2008. Main Exposures:We created a composite index of the social environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 53 publications
1
47
1
Order By: Relevance
“…However, evidence is growing that policies protecting and/or affirming sexual minorities have a protective impact on mental health44 and, in a paper published after our search, are associated with reduced adolescent tobacco initiation among sexual minorities 95. Evidence-based strategies such as tobacco tax increases, advertising limits, integrated mass-media campaigns, point of sale restrictions and tobacco-free places and spaces continue to be important areas of intervention for researchers, practitioners and community leaders to consider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence is growing that policies protecting and/or affirming sexual minorities have a protective impact on mental health44 and, in a paper published after our search, are associated with reduced adolescent tobacco initiation among sexual minorities 95. Evidence-based strategies such as tobacco tax increases, advertising limits, integrated mass-media campaigns, point of sale restrictions and tobacco-free places and spaces continue to be important areas of intervention for researchers, practitioners and community leaders to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, longitudinal studies are strongly suited to gain evidence of causation, however only two studies used longitudinal data. Third, resiliency (eg, supportive family environment) and protective factors are understudied areas of sexual minority research and may be of key importance since, even though sexual minorities have higher smoking prevalence than heterosexuals, the majority of sexual minority persons do not smoke 95 105. Fourth, additional theoretical approaches beyond minority stress may yield new insights.…”
Section: Discussionmentioning
confidence: 99%
“…42 Based on data from other countries, these disparities might be attributable to minority stress, healthcare discrimination, and lack of LGBT-specific medical expertise. 22,25,40,[43][44][45][46][47][48][49][50] By targeting mental health concerns through psychosocial interventions, physical health risk behaviors are concomitantly addressed. 51,52 LGBT-competent mental healthcare, which is urgently needed given LGBT individuals' elevated prevalence of psychiatric disorders, 22,[25][26][27][28]30,53 is lacking in Romania (LelutiuWeinberger C, Manu M, Lȃscut F, et al: Preliminary efficacy of the first mobile health intervention to reduce HIV risk among MSM in Romania.…”
Section: Introductionmentioning
confidence: 99%
“…While some work has begun investigating specifics of how the social environment may influence LGBT tobacco use,29 tobacco in the media environment has only been examined in a few studies that found tobacco images normative in the LGBT press 30 31. The media environment long made LGBT lives invisible, although there are increasingly visible LGBT narratives and characters.…”
Section: Resultsmentioning
confidence: 99%